2022
DOI: 10.21470/1678-9741-2020-0710
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity and Cellular Viability of Cryopreserved Allograft Heart Valves in Right Ventricular Outflow Tract Reconstruction: Correlation of Histopathological Changes with Donor Characteristics and Preservation Times

Abstract: Introduction Cryopreserved allograft heart valves (CAHV) show longer event-free survival compared to other types of protheses. However, all patients develop early and/or late allograft failure. Negative predictors are clinical, and there is a lack of evidence whether they correspond with the microscopic structure of CAHV. We assessed histopathological signs of structural degeneration, degree of cellular preservation, and presence of antigen-presenting cells (APC) in CAHV and correlated the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Of note, the difference between cryopreservation and cold static storage at 4 °C might be insignificant if cryopreservation is preceded with a long period of storage at 4 °C. To illustrate, this was reported to be the case in a recent study with a period of up to 28 days of storage at 4 °C before cryopreservation (Fabian, et al 2022 ). Despite the inconsistencies in literature regarding differences in cryopreserved or fresh valves, it is important to note that neither short-term cold static storage at 4 °C nor cryopreservation leads to the implantation of viable valves with growth potential.…”
Section: Classic Preservation Methodsmentioning
confidence: 83%
See 3 more Smart Citations
“…Of note, the difference between cryopreservation and cold static storage at 4 °C might be insignificant if cryopreservation is preceded with a long period of storage at 4 °C. To illustrate, this was reported to be the case in a recent study with a period of up to 28 days of storage at 4 °C before cryopreservation (Fabian, et al 2022 ). Despite the inconsistencies in literature regarding differences in cryopreserved or fresh valves, it is important to note that neither short-term cold static storage at 4 °C nor cryopreservation leads to the implantation of viable valves with growth potential.…”
Section: Classic Preservation Methodsmentioning
confidence: 83%
“…DMEM or RPMI-1640 media supplemented with foetal calf serum or HEPES (Lang et al 1994 ; Gerson et al 2009 )) although most studies do not report the preservation solutions used. It is important to note that valves preserved via this method are named “fresh valves” in literature (Schenke-Layland et al 2006 ; Fabian, et al 2022 ; Koolbergen et al 2002 ), (O’Brien et al 1987 ) despite the frequently observed loss of valve viability and loss of valve functionality compared to valves directly after extraction (Burkert et al 2008 ). Therefore, we believe that preservation at 4 °C for periods up to 95 days is unlikely to reflect the functionality and viability of fresh valves.…”
Section: Classic Preservation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collagen degeneration signs have previously been shown in vascular diseases such as aortic aneurysm and hypertension, and consist of increased waviness and disrupted fiber orientation, as well as disrupted D-bands with reduced contrast (Jones et al 2020 ). So far, studies have shown that mechanical and morphological properties of the extracellular matrix of the homograft vessel walls and cusps seem to keep intact after prolonged cold ischemic time prior to organ harvest (Smit et al 2015 ; Bester et al 2018 ; Fabian et al 2022 ). Forensic studies have shown that tissues with extracellular matrix that is rich in collagen and/or elastin, such as blood vessels, are resistant to both autolytic degeneration and microbiological decomposition and that adequate cooling slow the process even further (Cocariu et al 2016 ; Javan et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%